Methods of surfactant administration in newborn. Literature review - Głoskowska, Julia; Frańczuk, Agata; Kuleta, Katarzyna; Dyl, Tomasz; Kruk, Adrian; Gruszczyńska, Hanna; Szpulak, Angelika; Kopczyńska, Ewelina; Makłowicz, Aleksandra; Peregrym, Michał (Quality in Sport, 2024)
The most common cause of respiratory distress syndrome (RDS) in neonates born prematurely is surfactant deficiency. Surfactant administration has been the method of choice for the treatment of RDS since the 1990s, only the method of delivery is changing with the use of increasingly less invasive methods of respiratory support in neonatal respiratory failure. For many years, the standard method was the administration of surfactant after intubation through an endotracheal tube during artificial ventilation. Gradually, new methods were introduced to reduce or avoid the use of ventilation (INSURE), followed by methods that bypass intubation (LISA). The latest SALSA technique made it possible to omit the use of a laryngoscope and the need for intubation. The new methods of surfactant administration can be used successfully in newborns requiring only non-invasive respiratory support, in neonatal centers in regions with limited access to specialized medical care.